The Relationship Between the Level of Knowledge About Menopause with the Level of Menopausal Complaints in Leling Village, Tommo Subdistrict - Manuntungi, Andi Ernawati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
In the course of her life, women experience many processes of growth and development, until one day growth and development will stop at a stage so that too many changes occur in the function of the female body. These changes will occur as age increases until finally women will reach a point called menopause and at this point anxiety will arise because they feel they are no longer beautiful. In women facing the menopause period, the appearance of psychological symptoms is strongly influenced by changes in the physical-physiological aspects as a result of the reduction and cessation of estrogen hormone production. In women who experience premenopause, complaints that are often felt include: feeling anxious, fearful, irritable, irritable, difficult, concentration, nervous, feeling useless, worthless, stressed and some even experience depression.This research was conducted in Leling Village, Tommo Sub-District, Mamuju Regency from October to November 2022. By using descriptive analytic method using cross sectional study design with a total sample of 33 menopausal women with inclusion criteria: Menopausal mothers who are willing to become respondents and live in Leling village, Tommo sub-district, Mamuju district, menopausal mothers aged 45-54 years, menopausal mothers with good consciousness, not impaired hearing and vision, able to communicate well. Data collection using a questionnaire. Using the Chi-Square Statistical Test with a significance level of α = 0.05. Data analysis was performed by univariate analysis and bivariate analysis on the SPSS program. The results showed that: there was a relationship between the level of knowledge and the level of menopausal complaints in Leling Village, Tommo District, Mamuju Regency, 2022. with a value of p = 0.006 < the value of a = 0.05.